2023
DOI: 10.21203/rs.3.rs-2535734/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Burden of Ocular Morbidities Among Elderly Patients Visiting a District Healthcare Facility in Malawi

Abstract: Background: The population of older adults is growing dramatically. Sadly, this populace is highly prone to develop various ocular morbidities, which if left unattended can lead to blindness. Aim: To determine the distribution of ocular morbidities among older adults at a secondary hospital in Malawi. Methods: This was a retrospective cross-sectional study conducted at Mzimba North District Hospital in Malawi. We retrieved 314 patient records from the hospital’s ophthalmic outpatient registry from August 2020 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Our study found that Cataracts are the second common ocular disorder in contrast to a previous study 12 which found that cataract was a common ocular morbidity. The difference can be explained by differences in eye care staff composition between the two study settings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study found that Cataracts are the second common ocular disorder in contrast to a previous study 12 which found that cataract was a common ocular morbidity. The difference can be explained by differences in eye care staff composition between the two study settings.…”
Section: Discussioncontrasting
confidence: 99%
“…10 The pattern of ocular disease varies from country to country and even in the same country from district to district. 11 Previous studies have assessed the distribution of eye diseases at government hospitals, 8,12,13 however, there is no baseline data on the pattern of ocular morbidity among the Malawian elderly visiting nongovernment facilities. In Malawi, health services are provided for free at government facilities while private for-profit and private nonprofit organizations charge fees.…”
mentioning
confidence: 99%
“…In this review, more females than males visited the clinic with ocular morbidities similar to the pattern observed at a government health facility in the district [12]. In contrast, Kang and colleagues found that more males attend eye care services in Kasungu, Malawi [8].…”
Section: Discussionmentioning
confidence: 77%
“…The pattern of ocular disease varies from country to country and even in the same country from district to district [11]. Previous studies have assessed the distribution of eye diseases at government hospitals, [8,12,13] however, there is no baseline data on the pattern of ocular morbidity among the Malawian elderly visiting non-government facilities. In Malawi, health services are provided for free at government facilities while private for-pro t and private non-pro t organizations charge fees [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although eye care services are provided freely at the point of access as part of the Essential Health Package, Malawians still incur transportation costs. 30 Therefore, this study highlights the role of outreach eye screening programs in high-risk population groups. 31,32 Elsewhere, the most common ocular problem was refractive error.…”
Section: Discussionmentioning
confidence: 84%